Determinants of demand for reinsurance: An empirical analysis based on China’s property insurance companies - ZHANG, NANA (2017)
This study aims to research the determinants of the demand for reinsurance used by China’s property insurance companies combining micro and macro perspectives. The data from 49 property insurance companies during the period of 2008 to 2015 is used to conduct correlation and multi regression analysis. The empirical results indicate that the scale of an insurance company, its capital structure and its underwriting capacity are significant factors influencing its reinsurance decision. By contrast, the factors, such as the tax avoidance effect of reinsurance, the insurance company’s profitability, the concentration of business service and geography, cannot significantly affect the demand for reinsurance. In the macro view, the money supply and the catastrophe can stimulate the demand for reinsurance sharp increase while the state of insurance industry does not play an essential role in this research period.